Kenya's 2013 General Election : Stakes, Practices and Outcomes - Njogu, Kimani; Wekesa, Peter Wafula (Twaweza Communications, Ltd., 2015)
When voters enthusiastically turn up to cast their vote during general elections, they expect that their action would meaningfully change their lives. But in most of Africa, even when elections are held on a regular basis, voters are quite often disappointed by the performance of their leaders who use the new positions as an opportunity to loot public resources and consolidate power. It is almost as if elections are of minimal value to the populace. Notwithstanding this trend, when they are free and fair, general elections can be transformative. They can bring into the political arena men and women of integrity committed to service and account-ability. Inspired by the determination to have inclusive governance and the advancement of democracy, Kenya's 2013 General Election: Stakes, Practices and Outcomes asks important questions related to political participation, coalition building, politics of identity, the international criminal court, electoral systems and institutions, and the judiciary. The papers are written by mainly Kenyan academics and civil society actors who examine the drivers of the 2013 general elections and the sources of the mandate to lead.This book is part of publications by Twaweza Communications on democratic practice and accountable governance in Kenya.